IMPLEMENTASI PEMBINAAN WARGA JEMAAT KEPADA WARGA BINAAN KRISTEN DI LAPAS KELAS IIA PONTIANAK - Sumarlina, Ketty (STT Ekklesia Pontianak, 2023)
Abtract: The treatment should be done by church as organization which accomodate spirituality activity accordance to Lord Jesus teachings because congregational members also as church members which is in out of line condition of the truth of God’s word andtother various pressures. As person who break government rules and undergo a life as prisoner with limited right he should be treated in order to realize his faults and may undergo life accordance to government regulation, and especially to the truth of God’s Word. The treatment to church members at jail not only including spirituality activity, however also the treatment to all aspects of the human themselves. This research describes the implementation to congregational members including the faith treatment, mental and skills treatment. The problems analyzed relate to the implementation of the treatment forms to congregational members such as the faith treatment, mental and skills treatment to church members at prison class IIA Pontianak. This is a descriptive study using observation, interview, and documentation. The outcome of this congregational members treatment is able to increase the spirituality of the knowledge of god and God’s word, able to increase mental and self-confidence, and increase the income of their work, also increase the society support to christian prisoners at class IIA prison in Pontianak. Key words: Implementation, congregational members treatment